Mapping And Measuring Digital Literacy In Secondary Education Through Systematic Literature Review Of Psychometric And Implication - Kumala Sari, Via Indriani; Djuniadi; Isnaeni, Wiwi; Rusilowati, Ani (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
The rapid advancement of digital technology has profoundly transformed education and other aspects of life. In the 21st century, digital literacy has become a core competence for secondary school students to navigate academic, social, and professional environments. However, assessment efforts remain inconsistent, as most instruments are designed for university students or teachers. This study aims to identify and analyze research on digital literacy assessment instruments for secondary education through a Systematic Literature Review (SLR) following the PRISMA protocol. Guided by the PICOS framework, 22 articles published between 2021 and 2025 were selected from six international databases (Scopus, ERIC, Google Scholar, SpringerLink, Garuda, and DOAJ Indonesia). The findings demonstrate a rapid increase in research on digital literacy assessment, with the DigComp 2.1 and UNESCO MIL frameworks being the most widely adopted, while several countries, including Indonesia, have developed localized models. Psychometric analyses reveal a methodological shift toward modern approaches such as the Rasch Model, Confirmatory Factor Analysis (CFA), and Aiken’s V, ensuring stronger construct validity. These findings underscore significant implications for curriculum development, educational policy, and learning strategies. Overall, this study strengthens the conceptual and psychometric foundations of digital literacy assessment and offers strategic guidance for developing valid, reliable, and contextually grounded instruments to enhance education in the digital era.